Pleomorphic Adenoma versus Basal Cell Adenoma: An immunohistochemical analysis with b-catenin - Prado, Renata Falchete do; Cardoso, Camila Lopes; Consolaro, Alberto; Taveira, Antonio Luis Assis (Brazilian Dental Science, 2014)
The objective of this study was to investigate the distribution of b-catenin in pleomorphic adenomas and the basal cell adenomas to clarify its possible role in the etiopathogenesis of these two lesions. The expression of b-catenin (BD Transduction Laboratories) was analyzed by immunohistochemistry in formalin-fixed, paraffin-embedded specimens by the avidin-biotin-peroxidase complex method in 10 pleomorphic adenomas and 2 basal cell adenomas. The specimens were analyzed taking into account intensity, distribution and association with myoepithelial cells. The results showed that all cases of pleomorphic adenomas exhibited membranous and cytoplasmic immunostaining and the 2 cases of basal cell adenomas displayed nuclear staining. Higher b-catenin index rates were seen mainly in ductal structures of pleomorphic adenomas and in the nuclei of myoepithelial stromal and myoepithelial cells of solid clusters in basal cell adenomas. In conclusion, this immunohistochemical study may suggests the different degree of differentiation of the myoepithelial cells in these two tumors.